2021
DOI: 10.3389/fgene.2021.743133
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis Changes the Microenvironment and Therapeutic Response Under the Driver of Gene Mutation in Esophageal Adenocarcinoma

Abstract: Background: Esophageal cancer is one of the most leading and lethal malignancies. Glycolysis and the tumor microenvironment (TME) are responsible for cancer progressions. We aimed to study the relationships between glycolysis, TME, and therapeutic response in esophageal adenocarcinoma (EAC).Materials and Methods: We used the ESTIMATE algorithm to divide EAC patients into ESTIMATE high and ESTIMATE low groups based on the gene expression data downloaded from TCGA. Weighted gene co-expression network analysis (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Inhibiting the HH pathway was linked to fewer cells with a cancer stem cellassociated phenotype (CD44+/CD24-), decreased spheroid formation, and increased radiosensitivity, according to a recent study (Wang et al, 2019). The glycolytic pathway is important in the occurrence and progression of esophageal cancer (Zhu et al, 2021). Previous research has shown that glycolysis can affect EAC immunotherapy by altering the microenvironment caused by genetic mutations (Zhu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibiting the HH pathway was linked to fewer cells with a cancer stem cellassociated phenotype (CD44+/CD24-), decreased spheroid formation, and increased radiosensitivity, according to a recent study (Wang et al, 2019). The glycolytic pathway is important in the occurrence and progression of esophageal cancer (Zhu et al, 2021). Previous research has shown that glycolysis can affect EAC immunotherapy by altering the microenvironment caused by genetic mutations (Zhu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The glycolytic pathway is important in the occurrence and progression of esophageal cancer (Zhu et al, 2021). Previous research has shown that glycolysis can affect EAC immunotherapy by altering the microenvironment caused by genetic mutations (Zhu et al, 2021). CLDN9, GFPT1, HMMR, RARS, and STMN1 are glycolysis-related gene signatures that predict prognosis in patients with esophageal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation should be extended to the cancer microenvironment when translating the results of cancer responses to in vivo studies. The cancer microenvironment, which includes neighboring cells, blood vessels, and the extracellular matrix, can affect the expression of glycolysis-related genes 20 , 21 , limit drug delivery to tumor cells, and alter the immune response to the tumor 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This explanation should be extended to the cancer microenvironment when translating the results of cancer responses to in vivo studies. Thus, we should mention that the cancer microenvironment, which includes neighboring cells, blood vessels, and the extracellular matrix, can affect the expression of glycolysis-related genes 20,21 , limit drug delivery to tumor cells, and alter the immune response to the tumor 22,23 .…”
Section: Discussionmentioning
confidence: 99%